2007
DOI: 10.1080/02668730701535610
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Short‐term Psychodynamic Art Therapy Compared to Short‐term Psychodynamic Verbal Therapy for Depressed Women

Abstract: The primary aim of this randomized controlled clinical trial was to compare the outcome from two types of short-term psychodynamic psychotherapy. The participants were thirtynine women with depression. Half of the participants (n518) received art psychotherapy and the other half received verbal psychotherapy (n521). Data was collected before and after psychotherapy, and at a 3-month follow-up using self-rating scales and interviewer-based ratings. Results showed that art and verbal psychotherapies were compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 19 publications
2
68
1
Order By: Relevance
“…Similar results were obtained from a number of arts therapies studies (Erkkilä et al, 2011;Jeong et al, 2005;Thyme et al, 2007). While the current study did not include a control group, it may not be concluded with certainty whether this effect occurred as an implication to the therapy or whether it was due to other reasons, including a possible spontaneous recovery from depression (Ankarberg & Falkenström, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…Similar results were obtained from a number of arts therapies studies (Erkkilä et al, 2011;Jeong et al, 2005;Thyme et al, 2007). While the current study did not include a control group, it may not be concluded with certainty whether this effect occurred as an implication to the therapy or whether it was due to other reasons, including a possible spontaneous recovery from depression (Ankarberg & Falkenström, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…[47][48][49] Of these three studies, only one was conducted in adults. 47 In the remaining 12 studies, the study population comprised individuals without a formal mental health diagnosis.…”
Section: Included Studies: Quantitative Reviewmentioning
confidence: 99%
“…[47][48][49] Of these three studies, only one was conducted in adults. 47 In the remaining 12 studies, the study population comprised individuals without a formal mental health diagnosis. [49][50][51][52][53][54][55][56][57][58][59]61,62 The populations in these studies are, therefore, mainly people with long-term medical conditions which are not reported to be accompanied by a mental health diagnosis; however, outcomes targeted in these studies were mental health symptoms.…”
Section: Included Studies: Quantitative Reviewmentioning
confidence: 99%
See 2 more Smart Citations